Pretreatment Serum Albumin and Neutrophil-to-Lymphocyte Ratio for Predicting Overall Survival in Esophageal Cancer Patients - Wen JIANG; Jiali XU; Yongqian SHU; Hongliang GUI; Tingting WANG; Lianke LIU; Rong WANG (国际转化医学杂志（英文版）, 2019)
Purpose: The aim of the study was to elucidate the prognostic impacts of pretreatment hematology markers, such as neutrophil-to-lymphocyte ratio (NLR), albumin (ALB), carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) in esophageal cancer (EC) patients. Methods: Data of 127 esophageal cancer patients who didn't receive chemotherapy between 2015 and 2017 were retrospectively documented. Based on the optimal cut-off value of NLR and ALB identified by generating receiver operating characteristics (ROC) curve, we classified the patients into two groups respectively. The clinicopathological parameters were compared between the two groups of NLR and ALB. Results: Kaplan-Meier analysis demonstrated overall survival (OS) was significantly longer in NLR<1.992 group than NLR≥1.992 group (31 months vs. 13 months, P < 0.001) and in ALB≥39.95 g/L group than ALB<39.95 g/L group (31 months vs. 15 months, P = 0.002). NLR and ALB were independent prognostic factors for OS in the multivariate Cox regression model (HR =2.82, 95％CI: 1.59-5.01, P < 0.001 for NLR; HR = 0.59, 95％CI: 0.3-1.01, P = 0.055 for ALB). Conclusion: Pretreatment NLR and ALB could be independent prognostic biomarkers for OS in esophageal cancer patients.